KEGIATAN PUBLIC RELATIONS OLEH SALES MANAGER DALAM PEMBENTUKAN CITRA DI HOTEL IBIS BUDGET SURABAYA - Adi, Oetomo Yanus Ramadhan Putera; Sudaryanto, Edy; Pratiwi, Ni Made Ida (representamen, 2015)
Hotel is a bussiness utilizing a building equipped with facilities which are specially provided for theneeds of everybody who will stay or spend the night with adequate services and in return there arecharges for the services obtained. These things will also determine how many stars it deserves. The morestars achieved the better the image shown to the people. Therefore there's a certain division responsiblein building image for the company related, known as Public Relations. But does every company haveone? One of the starred hotels in Surabaya, Launched in july 1st 2013 with its one of a kind designand location is The Ibis Budget. It's where you'll find every rooms adapting the concept of design cocoonroom (which has won the hotel room design competition in Europe) and it's also located in a uniqueplace, none other than inside the Terminal 1 of Juanda International Airport. Another intriguing thingabout The Ibis Budget is its organizational structure that shows no sign of Public Relations. Neverthelessit seems that many people are still interested on the image it builds by itself. According to SS and EA,there are four components that needs to be done and determines the company image: cognition,perception, attitude, and motivation (S, 2003). And after this qualitative descriptive research is donethrough interview and field observation, the datas collected concludes that the Sales Manager only runsthree out of the four components (which are cognition, perception, and motivation) and there's no suchdivision as Public Relations. However the Ibis Budget Hotel still projects a good image to the people.Keywords: public relations activity, sales manager, image, hote